Attitude towards working in rural areas after graduation among undergraduates from various programs at Chitwan Medical College, Nepal - Lamsal, Pooja; Bajracharya, Subina (Journal of Chitwan Medical College, 2025)
Introduction: Most health professionals do not want to work in poorly served rural areas, and many graduates choose to leave the country for better opportunity. This study aimed to assess the attitude towards working in rural areas after graduation among undergraduate students of in Chitwan Medical College, Nepal. Method: A descriptive cross-sectional study was conducted among final-year medical and nursing students of Chitwan Medical College, Nepal from 19 Dec 2023 to 02 Jan 2024. Ethical approval was obtained. A self-administered questionnaire was used to participants selected by stratified proportionate sampling. Descriptive analysis (frequency, percentage, median, interquartile range) for socio-demographic variables and inferential (Chi-square, Fisher's exact test) statistics for association was conducted for association. A p≤0.05 was considered significant. Result: Out of 108 undergraduates (medical 65, nursing 43), 60(55.6%) had a positive attitude towards working in rural areas after graduation. Among the four domains assessed, student’s attitude was higher in profession-related factors with a median percentage of 65 and was lowest in work-related factors with a median percentage of 56. Significant association was found between father's occupation and students' attitude status (p=0.049). Conclusion: More than half of the undergraduate students in this study had a positive attitude towards working in rural areas. Further study is needed to explore effective intervention like improving facilities, security to enhance the positive attitude of students to serve in rural areas.